2019
DOI: 10.1002/eji.201848056
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on the interleukin‐1 family as targets for inflammatory disease

Abstract: Since the first description of interleukin-1 (IL-1) and the genesis of the field of cytokine biology, the understanding of how IL-1 and related cytokines play central orchestrating roles in the inflammatory response has been an area of intense investigation. As a consequence of these endeavours, specific strategies have been developed to target the function of the IL-1 family in human disease realizing significant impacts for patients. While the most significant advances to date have been associated with inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 164 publications
(181 reference statements)
1
32
0
2
Order By: Relevance
“…Further research, including different populations, is needed. The IL‐1 family of cytokines has been targeting by many researches in order to discover a therapeutic for patients with inflammatory diseases 43 . If +3954 C/T IL‐1β and/or higher levels of IL‐1 are present in patients with BMS, they can be relevant biomarkers, which may cause not only greater inflammation, but also aggravate BMS.…”
Section: Discussionmentioning
confidence: 99%
“…Further research, including different populations, is needed. The IL‐1 family of cytokines has been targeting by many researches in order to discover a therapeutic for patients with inflammatory diseases 43 . If +3954 C/T IL‐1β and/or higher levels of IL‐1 are present in patients with BMS, they can be relevant biomarkers, which may cause not only greater inflammation, but also aggravate BMS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that IL-36 family cytokines can promote their own expression in inflamed skin and possibly act in a feed forward fashion, in tandem with other pathogenic cytokines, to perpetuate inflammation and disease pathogenesis (Milora et al, 2015;Hernandez-Santana et al, 2019;Madonna et al, 2019). Therefore, we investigated whether loss of IL-36r activity among keratinocytes might alter the induction of IL-36 family gene expression in inflamed skin.…”
Section: Expression Of Il36r On Keratinocytes Is Required For the Actmentioning
confidence: 98%
“…It was first described in the late 1970s, and is considered a pivotal cytokine of the innate immune system. Indeed, therapies that block IL‐1 pathways are entering the clinic for a wide range of inflammatory syndromes …”
Section: Interleukin‐1 a Pivotal Cytokine Of The Innate Immune Systemmentioning
confidence: 99%
“…Indeed, therapies that block IL-1 pathways are entering the clinic for a wide range of inflammatory syndromes. 7 IL-1 exists in two forms, IL-1α and IL-1β, both of which are synthesized as ~33-kDa precursors that can be processed via proteolytic cleavage, to mature cytokines. 8 Our focus is on IL-1α, a key initiating pro-inflammatory factor, implicated in the pathogenesis/progression of several major disorders, including cardiovascular disease, neural inflammation, inflammatory bowel disease, atherosclerosis, and cancer.…”
Section: Interleuk In -1 a Pivotal C Y Tok Ine Of The Innate Immumentioning
confidence: 99%